Les concours de beauté amérindiens. Nouvelles formes de spectacularisation de l’indianité - Magda Helena Dziubinska (Centre de Recherches sur les Mondes Américains, 2017)
Beauty contests, increasingly popular among Amerindian groups, have today become the central element of festivals in which indigenous peoples are the main actors (such as The Day of the Indian in Brazil, patronage festivals in Guatemala, and native community anniversaries in Peru, etc.). The purpose of this presentation is twofold. Firstly, it explores the different representations of autochthony that are displayed during these events, and the connections between competition and processes of cultural objectification and revalorization. Secondly, drawing on contrastive cases it addresses the different relational configurations in which Amerindian groups engage with national societies. I propose that beauty contests are not a mere emanation of these relations but, on the contrary, constitute a space in which these relations are invented, constructed and negotiated.